-(5a+6)=-2(3a+8)

Simple and best practice solution for -(5a+6)=-2(3a+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5a+6)=-2(3a+8) equation:


Simplifying
-1(5a + 6) = -2(3a + 8)

Reorder the terms:
-1(6 + 5a) = -2(3a + 8)
(6 * -1 + 5a * -1) = -2(3a + 8)
(-6 + -5a) = -2(3a + 8)

Reorder the terms:
-6 + -5a = -2(8 + 3a)
-6 + -5a = (8 * -2 + 3a * -2)
-6 + -5a = (-16 + -6a)

Solving
-6 + -5a = -16 + -6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6a' to each side of the equation.
-6 + -5a + 6a = -16 + -6a + 6a

Combine like terms: -5a + 6a = 1a
-6 + 1a = -16 + -6a + 6a

Combine like terms: -6a + 6a = 0
-6 + 1a = -16 + 0
-6 + 1a = -16

Add '6' to each side of the equation.
-6 + 6 + 1a = -16 + 6

Combine like terms: -6 + 6 = 0
0 + 1a = -16 + 6
1a = -16 + 6

Combine like terms: -16 + 6 = -10
1a = -10

Divide each side by '1'.
a = -10

Simplifying
a = -10

See similar equations:

| x-0.25x=22.50 | | 4x^3-6x^2-72x+48=0 | | 10a^4b^2/15a^2b^3c^2 | | 9x+25= | | 394/2000 | | (2x+1)*2x=20 | | 2x(2x^2+24x+27)=0 | | 3x+4x-5x+6=0 | | Ln(x)-2x=0 | | ln(x)=2x | | lnx=2x | | 7x+8x-3x+6=0 | | -3x+5x=18 | | 25-5/17 | | 3x(2-x)-5(6-2x)=0 | | 13/5/5 | | 0.07m=0.4x | | 13/5//5 | | 1/5(x=2=-3 | | (16-x2)-5/9 | | 2/3x-1=3/7 | | -1/3y=3 | | 9-8i= | | 7(x+3)-(6x-9)=2 | | 1/2-7i | | ln(x-8)-ln(x+2)=ln(11) | | (3x+2)(x+2)=4 | | 32.4=4p | | e^4-5x=3 | | 25x+24x+5=180 | | m/2.6=3.5 | | 32n=99.2 |

Equations solver categories